Paradox in Disaster Management: 2020 Aegean Sea Earthquake - Alper Bilgili; Gaye Sanatcı Aktaş (Doğal Afetler ve Çevre Dergisi)
The paradigm shift in the understanding of public administration has brought some changes in disaster management as well. Instead of a command-control-based centralized and bureaucratic disaster management approach that requires bureaucratic expertise, a multi-actor and solidarist disaster management approach, in which authorities and responsibilities are not constructed from top to bottom, has gained weight. In this context, it was determined as the problem of the research that "determining which of the centralist/bureaucratic disaster management and multi-actor/solidarity disaster management models are mainly applied in disaster management policies", and in this context, "decision-making authority and implementation responsibility regarding disaster management are central government, local governments and how is it shared among non-governmental organizations?”. The answer to this question has been sought. The research includes the analysis of the 2020 Aegean Sea Earthquake, which was recorded as the deadliest earthquake among the earthquakes that occurred in the world in 2020, in the form of content analysis with the MAXQDA Analytics Pro 20 program, which is used in the analysis of qualitative and mixed methods. The data used in the research: 30-31 October and 1 November belonging to the official Twitter accounts of the Izmir Governor's Office and the Disaster and Emergency Management Presidency within the scope of the central government, and AKUT and IHH Humanitarian Relief Foundation within the scope of the non-governmental organizations of the Izmir Metropolitan Municipality and Seferihisar Municipality within the scope of local administrations. It includes posts from 2020. As a result of the research, it has been concluded that the multi-actor/solidarist disaster management approach is included in the policy documents, but in the event of a disaster, the authority and responsibility are mainly carried out under the control of the central government.